Adding intensity-modulated radiotherapy to the pelvis does not worsen the adverse effect profiles compared to limited field radiotherapy in men with prostate cancer at 12-month follow-up. (October 2014) - Lilleby, Wolfgang; Stensvold, Andreas; Dahl, Alv A.
Abstract To compare adverse effects and toxicity in men with high-risk or locally advanced prostate cancer when adding intensity-modulated radiotherapy (IMRT) technique to the pelvis. Patients and methods. In this prospective follow-up study 180 patients treated with conformal radiotherapy (RAD) to the prostate and vesiculae seminales (boost volumes; PV) and long-term androgen deprivation therapy (LADT), were compared to 90 patients managed by LADT, RAD to the PV and additionally pelvic IMRT. Adverse effects were self-reported at baseline, at 3- and 12-month follow-up. At each time point, the patients rated a questionnaire covering urinary, bowel, and sexual function and bother, quality of life, fatigue, and mental distress. Results. At 3-month follow-up urinary and bowel functions were significantly decreased among IMRT compared to RAD. At 12-month follow-up both groups showed the same reductions within the urinary, bowel and sexual domains. RAD patients had more mental distress than IMRT patients. The scores on quality of life, fatigue and mental distress hardly influenced function or bother within the urinary, bowel or sexual domains. Conclusions. Men treated for high-risk or locally advanced prostate cancer with a combination of LADT, RAD and IMRT including PV and pelvic structures had considerably more acute side effects at 3 months than men treated with LADT and RAD to the PV only. However, at 12-month follow-up, the observed genitourinary and gastrointestinal function and bother were similar in both groups.